Late swing or early stance? A narrative review of hamstring injury mechanisms during high-speed running - Kenneally-Dabrowski, C. J. B.; Brown, N. A. T.; Lai, A. K. M.; Perriman, D.; Spratford, W.; Serpell, B. G. (Scandinavian Journal of Medicine & Science in Sports, 2019)
Hamstring injuries are highly prevalent in many running-based sports, and predominantly affect the long head of biceps femoris. Re-injury rates are also high and together lead to considerable time lost from sport. However, the mechanisms for hamstring injury during high-speed running are still not fully understood. Therefore, the aim of this review was to summarize the current literature describing hamstring musculotendon mechanics and electromyography activity during high-speed running, and how they may relate to injury risk. The large eccentric contraction, characterized by peak musculotendon strain and negative work during late swing phase is widely suggested to be potentially injurious. However, it is also argued that high hamstring loads resulting from large joint torques and ground reaction forces during early stance may cause injury. While direct evidence is still lacking, the majority of the literature suggests that the most likely timing of injury is the late swing phase. Future research should aim to prospectively examine the relationship between hamstring musculotendon dynamics and hamstring injury.